Pengaruh Likuiditas dan Profitabilitas terhadap Financial Distress - Gusmao, Cristino; Martins, Celeste Maria; Amaral, Leonardo Bele Bau; Sulistyawati, Ardiani Ika; Santoso, Aprih (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The study aims to find empirical evidence of the influence of liquidity (CR) and profitability (ROA) on financial distress. In this study, the researcher used a quantitative method using panel data regression. The study population consisted of companies listed on the Jakarta Islamic Index (JII 30) 2021-2024, and a purposive sampling technique was used to determine the sample size. A total of 84 samples from 21 companies were selected for this study. The data analysis technique used EViews 12. Based on the research findings, financial distress is significantly influenced by liquidity (CR) and profitability (ROA). The R-square results indicate that the influence of CR and ROA on financial distress, with a value of 0.8997 or 89.97%, is included in the high category. Meanwhile, other variables not studied may have an influence of 10.03%.